2022
DOI: 10.1177/01423312221138841
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive power distribution scheme for hybrid energy storage system to reduce the battery energy throughput in electric vehicles

Abstract: The battery/supercapacitor (SC) hybrid energy storage system (HESS) is widely applied in electric vehicles (EVs) in recent years due to the hybrid system which combines the benefits of both devices. This paper proposes an adaptive power distribution scheme for battery/SC HESS to maximise the usage of SC according to its stored energy and load current. In the approach, the low-pass filter is developed with adaptive algorithm to calculate the suitable cut-off frequency to allocate the power demand between the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Taking into account the aforementioned points (i) to (iii) it can be concluded that a heat pump-based thermal management system of EVs has the dual objective of (a) stabilizing temperature in the passengers' cabin at the desirable levels so as to ensure the passengers' comfort and (b) stabilizing temperature at the batteries' side so as to avoid degradation of the batteries power storage capacity and of their regenerative charging capability. To this end, some additional results on optimization of EVs heat pump-based thermal management system can be noted [26][27][28][29][30]. One can distinguish primarily the use of NMPC techniques for heat pump-based thermal management systems of EVs [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the aforementioned points (i) to (iii) it can be concluded that a heat pump-based thermal management system of EVs has the dual objective of (a) stabilizing temperature in the passengers' cabin at the desirable levels so as to ensure the passengers' comfort and (b) stabilizing temperature at the batteries' side so as to avoid degradation of the batteries power storage capacity and of their regenerative charging capability. To this end, some additional results on optimization of EVs heat pump-based thermal management system can be noted [26][27][28][29][30]. One can distinguish primarily the use of NMPC techniques for heat pump-based thermal management systems of EVs [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the aforementioned points (i) to (iii) it can be concluded that a heat pump-based thermal management system of EVs has the dual objective of (a) stabilizing temperature in the passengers' cabin at the desirable levels so as to ensure the passengers' comfort and (b) stabilizing temperature at the batteries' side so as to avoid degradation of the batteries power storage capacity and of their regenerative charging capability. To this end, some additional results on optimization of EVs heat pump-based thermal management system can be noted [26][27][28][29][30]. One can distinguish primarily the use of NMPC techniques for heat pump-based thermal management systems of EVs [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%